Coaching employee engagement training - Garber, Peter R. (ASTD trainer's workshop series., 2011)
"Coaching Employee Engagement Training is written for managers and other leaders who, regardless of their level of experience, wish to facilitate and support the development of truly engaged employees within their organization. Utilizing clear, focused suggestions on improving employee coaching skills, Coaching Employee Engagement Training focuses on the fundamentals of successful employee coaching, and delivers powerful, pragmatic lessons within an easy-to-use, highly efficient workbook format. With its comprehensive approach to teaching employee coaching, Coaching Employee Engagement Training is a valuable resource for everyone interested in creating a more engaged workplace environment. Creating and presenting highly effective training materials and methods. Tailoring your training to your specific audience. Choosing and implementing appropriate, applicable program formats. Utilizing the detailed lesson plans and user guides included in the book. Understanding the three levels of coaching communication. Deploying specific, detailed role-playing scenarios and suggestions. Objectively assessing and evaluating your training and coaching programs. More than just a manual, Coaching Employee Engagement Training is a complete resource offering in-depth lessons, suggestions, exercises, worksheets, and evaluation forms. Coaching Employee Engagement Training offers managers and leaders at every level of experience and organizational rank the tools needed to create and maintain a high degree of meaningful, organic employee engagement." -- Publisher.